Use and Perception of Electronic Cigarettes Among College Students - Trumbo, Craig W. (2013)
OBJECTIVE: This study provides insight into how electronic cigarettes may affect the social normative environment for tobacco use among college students. PARTICIPANTS: 244 freshman and sophomore students. METHODS: Students completed an online self-report survey in April 2011. RESULTS: There is a higher acceptance rate of e-cigarette smoking in public than traditional tobacco. For intention to use an e-cigarette the strongest predictor is current tobacco use, followed by a positive orientation toward public use of e-cigarettes. Positive orientation toward public use of e-cigarettes is significantly predicted by the use of alternate tobacco, intention to use or try e-cigarettes, positive orientation toward public use of tobacco, positive attitude toward e-cigarettes, positive perception of social norms for use of e-cigarettes, and favorable orientation toward e-cigarettes as an innovation. CONCLUSIONS: These models suggest attitudinal, social normative, innovation, and behavioral factors may combine to bring the electronic cigarette into wider use among college students.